Lab@Home: The Open University of Catalonia Hands-on Electronics Laboratory for Online Engineering Education - Monzo, Carlos; Cobo, Germán; Morán, José Antonio; Santamaría, Eugènia; García-Solórzano, David (Electronics (Basel), 2020)
Practical experimentation is essential for electronics learning. As the acquisition of practical and professional competences in full online scenario is concerned, it is very relevant the use of technology that allows students to carry out hands-on experiments. This paper presents Lab@Home, the Open University of Catalonia (Universitat Oberta de Catalunya, UOC, Barcelona, Spain) hands-on electronics laboratory, which allows online students to carry out practical experiments anywhere and anytime at a reduced cost and with good portability characteristics. Lab@Home features and students satisfaction are analyzed during six consecutive semesters in two different subjects by means of a self-administered questionnaire, showing the benefits of using Lab@Home in the acquisition of the subjects contents and gathering how could be improved students learning experience by using this kind of electronics laboratory.